2009
DOI: 10.1111/j.1600-0587.2009.05791.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between tree species seedling and adult altitudinal distribution in mountain forests during the recent warm period (1986–2006)

Abstract: Spatial fingerprints of climate change on tree species distribution are usually detected at latitudinal or altitudinal extremes (arctic or alpine tree line), where temperatures play a key role in tree species distribution. However, early detection of recent climate change effects on tree species distribution across the overall temperature gradient remains poorly explored. Within French mountain forests, we investigated altitudinal distribution differences between seedling (550 cm tall and 1 yr old) and adult (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
160
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(179 citation statements)
references
References 56 publications
(121 reference statements)
12
160
2
2
Order By: Relevance
“…Woodall et al (2009) found significant northward advances of saplings over trees in boreal species of North America. The fact that Lenoir et al (2009) found only insignificant advances of seedlings at upper limits in French mountains is attributable to the exclusion of plots in the treeline ecotone. The finding of these authors that seedlings have significantly higher low elevation limits than trees is not visible in the Bavarian Alps, giving no sign of range contraction induced by recent warming.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Woodall et al (2009) found significant northward advances of saplings over trees in boreal species of North America. The fact that Lenoir et al (2009) found only insignificant advances of seedlings at upper limits in French mountains is attributable to the exclusion of plots in the treeline ecotone. The finding of these authors that seedlings have significantly higher low elevation limits than trees is not visible in the Bavarian Alps, giving no sign of range contraction induced by recent warming.…”
Section: Discussionmentioning
confidence: 98%
“…Apparently, before the climate change debate, the study of tree species distributions was considered unrewarding. The present study demonstrates the value of high resolution observation databases in obtaining more explicit and exact information (Ewald 2001, Guisan et al 2007, Lenoir et al 2009, Dengler et al 2011 along the altitudinal gradient can be studied; (3) tree and regeneration occurrences can be discerned from layer information; and (4) plot locations can be intersected with spatially interpolated climate variables or re-visited for field measurements. Depending on the underlying sampling strategy, the sources differ in their potential to find upper limits of trees.…”
Section: Discussionmentioning
confidence: 99%
“…The changes we wish to detect might be the edges of distributions (Murphy et al 2010) or the means of distributions (Kelly and Goulden 2008, Lenoir et al 2009, Shoo et al 2006, but regardless, test statistics should be used that are robust to Type 1 errors in the face of sampling bias. This study has taken the approach of simulating data that is analogous to the type of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While it is not original to use museum specimens and historical surveys to search for evidence of shifts in species distribution in modern time (Kelly and Goulden 2008, Lenoir et al 2008, Lenoir et al 2009, Moritz et al 2008, Willis et al 2008) these studies have two distinct advantages that essentially moot the sample selection bias issues outlined above: they are based on intensive surveys that characterize both absence and presence; and the modern surveys are designed to resample the exact locales of the historic effort. To the extent that sampling intensity varies in time, presence/absence surveys can be stratified and resampled to ensure equal sampling intensity over time (Lenoir et al 2008, Shoo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Стійкість популяцій рідкісних видів рослин і тренди їх розвитку визначаються не тільки чисельністю особин (N), але й низкою інших важливих популяційних параметрів (Elderd et al, 2003;Lenoir et al, 2009;Hampe, 2011). До таких належать популяційна щільність (PD), індекс відновлюваності (IR), індекс генеративності (IG), віталітет популяції (Q), індекс віковості популяції (Δ), індекс ефективності популяції (ω).…”
Section: матеріал і методи дослідженьunclassified